2015
DOI: 10.1890/es14-00117.1
|View full text |Cite
|
Sign up to set email alerts
|

Indirect interactions in terrestrial plant communities: emerging patterns and research gaps

Abstract: Abstract. Indirect interactions occur when the effect of one species on another is mediated by a third species. These interactions occur in most multi-species assemblages and are diverse in their mechanistic pathways. The interest in indirect interactions has increased exponentially over the past three decades, in recognition of their importance in determining plant community dynamics and promoting species coexistence. Here, we review the literature on indirect interactions among plants published since 1990, u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
68
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(69 citation statements)
references
References 258 publications
1
68
0
Order By: Relevance
“…These processes can be diffused and undetectable at the species pair level, that is, when exploring only species pair patterns. Indirect interactions are assumed to play a key role in community assemblies by promoting diversity and coexistence (Sotomayor & Lortie ). In fact, in a related study, we found that although interspecific interactions did not appear to be driving the local distribution of the species in the community, this pattern did not necessarily scale up to the community level, where the species richness was well structured in multispecies clumps (Chacón‐Labella, de la Cruz & Escudero ).…”
Section: Discussionsupporting
confidence: 87%
“…These processes can be diffused and undetectable at the species pair level, that is, when exploring only species pair patterns. Indirect interactions are assumed to play a key role in community assemblies by promoting diversity and coexistence (Sotomayor & Lortie ). In fact, in a related study, we found that although interspecific interactions did not appear to be driving the local distribution of the species in the community, this pattern did not necessarily scale up to the community level, where the species richness was well structured in multispecies clumps (Chacón‐Labella, de la Cruz & Escudero ).…”
Section: Discussionsupporting
confidence: 87%
“…, , Moore et al. , Sotomayor and Lortie ). As a result of these indirect interactions, the effects of natural enemies on a species may depend as much on the community context of a host as on its inherent resistance or tolerance to an enemy (Holt et al.…”
Section: Introductionmentioning
confidence: 98%
“…As a result of these indirect interactions, the effects of natural enemies on a species may depend as much on the community context of a host as on its inherent resistance or tolerance to an enemy (Holt et al. , , Sotomayor and Lortie ). For example, the presence of a highly competent host in a community may increase pathogen prevalence (i.e., the spillover effect; Power and Mitchell ) and may ultimately reverse the competitive hierarchy among plant species (Borer et al.…”
Section: Introductionmentioning
confidence: 99%
“…The interactions between these role-players influence not only the organisms involved, but ecosystem functioning, as they combine to form complex networks at a range of scales . As the Anthropocene advances, indirect interactions (that is, the effects of one species on another, mediated by a third species) via pollination of terrestrial plants emerges as key to maintenance of biodiversity, ecosystem function, and agricultural production Sauve et al, 2016;Sotomayor and Lortie, 2015). This is because perturbations can have unforeseen consequences for a number of species via shared resources.…”
Section: Introductionmentioning
confidence: 99%
“…To date, most studies relating landuse to spillover effects have occurred in temperate, ecologically-transformed regions in the northern hemisphere (Henri et al, 2015;Sotomayor and Lortie, 2015). In addition, approximately half of the data used in thirteen recent meta-analyses on global pollination ecology were collected from only 5 developed countries, with the entire African continent contributing only 4% of the data (Archer et al, 2014).…”
Section: Introductionmentioning
confidence: 99%